Development of composing skills in Filipino among second graders through directed reading lessons - Reyes, Jo Anne S.; Pado, Felicitas E. (2013)
The study investigated the development of composing skills in Filipino among second graders through Directed Reading Lessons (DRLs). The guiding questions were: (1) Do the Directed Reading Lessons (DRLs) improve the composing skills in Filipino among Grade 2 children? (2) In what ways did the children's composing skills improve?

Ten children were conveniently selected and given twelve DRLs with three prior scaffold lessons. Writing samples were collected and analyzed using the writing rubrics of Fiderer (1998) and Rog (2007). The study revealed that DRLs can have a positive effect on children's composing skills. Good writing is the result of explicit, structured teaching of craft and convention, implicitly learned book language, and writing style as children write in response to stories they read or listen to in the context of repeated opportunities for practice.
Keywords: Literacy; Supervised study